2005
DOI: 10.1007/s10439-005-5367-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Complications Encountered with Arteriovenous Fistulas and Grafts as Vascular Access for Hemodialysis: A Review

Abstract: This review article describes the current state of affairs concerning in vivo, in vitro and in numero studies on the hemodynamics in vascular access for hemodialysis. The use and complications of autogenous and non-autogenous fistulas and catheters and access port devices are explained in the first part. The major hemodynamic complications are stenosis, initiated by intimal hyperplasia development, and thrombosis. The different in literature proposed conceivable causes of intimal hyperplasia development like s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 87 publications
5
86
0
10
Order By: Relevance
“…Patients with chronic renal failure who are undergoing hemodialysis require a dependable vascular puncture site so that regular angioaccess is possible, as this is often re- quired between two to five times per week allowing a flow rate of approximately 350 ml/minute [2]. Temporary dialysis relies on catheters inserted into large veins such as the jugular or femoral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with chronic renal failure who are undergoing hemodialysis require a dependable vascular puncture site so that regular angioaccess is possible, as this is often re- quired between two to five times per week allowing a flow rate of approximately 350 ml/minute [2]. Temporary dialysis relies on catheters inserted into large veins such as the jugular or femoral.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent access sites involve the use of indwelling catheters or port access devices, or the surgical manufacture of a communication between distal arteries and veins in an extremity. The latter may take several forms, with the use of autogenous vessels such as the cephalic vein anastomosed to the radial artery in the wrist, or the cephalic vein to the brachial artery in the upper arm, creating a native arteriovenous fistula (AVF) [2,3]. An alternative technique is to use a non-autogenous graft made of prosthetic material such as dacron, polyurethane or polytetrafluoroethylene, or from bovine vessels, or the saphenous vein, to form an arteriovenous graft (AVG).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis of AVF failure is largely extrapolated from studies of peripheral bypass grafts. Small animal studies have confirmed that haemodynamic changes associated with AVF formation promote similar pathobiological changes, in particular VSMC proliferation, migration and differentiation [18,19]. Figure 1 illustrates the underlying pathways of neointimal hyperplasia in AVF.…”
Section: Failure Of Mature Avfmentioning
confidence: 93%
“…In the meantime, it seems reasonable to give anticoagulant therapy to those patients with thrombotic tendency in order to reduce thrombotic complications. 14,15 FV Leiden and prothrombin G20210A mutations are the common risk factors contributing to the development of thrombosis. In this study, all patients were evaluated for the presence of FV Leiden and prothrombin G20210A mutations and other prothrombotic risk factors.…”
Section: Discussionmentioning
confidence: 99%